The Effectiveness of A Smart System-Based Trainer with Multi-Authentication in Enhancing Students’ Competence in Motorcycle Security Systems - Wabdillah; Syafiuddin Parenrengi; Muhammad Farid; Marthen Paloboran; Mansyur; Ahmad Kurniawan (Academic Bright Collaboration, 2026)
Purpose – This study examined the implementation of a smart system-based trainer with multi-authentication in vocational motorcycle security-system learning. The trainer integrated fingerprint recognition, voice command, and smartphone-based control to support authentic and practice-oriented learning activities in vocational automotive education. The study aimed to evaluate whether the trainer was associated with improvements in students’ cognitive and practical competence within the instructional context of the study. Methods – This research employed a quasi-experimental non-equivalent control group pretest-posttest design involving 60 students from the Motorcycle Business and Engineering Department at SMK Negeri 5 Gowa, Indonesia. The participants were divided into an experimental group and a control group using intact classroom assignment. Data were collected using competence tests, practical performance rubrics, observation sheets, and student response questionnaires. The data were analyzed using descriptive statistics, normalized gain (N-gain), assumption testing, and t-test analysis. Findings – The findings showed that the experimental group achieved higher posttest scores, stronger N-gain values, and better practical performance compared to the control group. The results also indicated more active classroom participation and positive student responses toward the instructional media in the experimental group. Research Implications – These findings suggest that the smart system-based trainer was associated with improved short-term cognitive and practical learning outcomes within the context of this classroom implementation. Originality – However, the findings should be interpreted cautiously because the study was conducted in one vocational school using non-randomized classroom groups and a relatively short intervention period. Therefore, the results represent initial empirical evidence rather than definitive proof of broad instructional effectiveness in vocational education.